Local and regional heterogeneity underlying hippocampal modulation of cognition and mood - Tannenholz, Lindsay; Jimenez, Jessica C.; Kheirbek, Mazen A. (Frontiers in Behavioral Neuroscience, 2014)
While the hippocampus (HPC) has been classically studied for its role in learning and memory, there is significant support for a role of the HPC in regulating emotional behavior. Emerging research suggests these functions may be segregated along the dorsoventral (DV) axis of the HPC. In addition to this regional heterogeneity, within the HPC, the dentate gyrus (DG) is one of two areas in the adult brain where stem cells continuously give rise to new neurons. This process can influence and be modulated by the emotional state of the animal, suggesting that adult neurogenesis within the DG may contribute to psychiatric disorders and cognitive abilities. Yet, the exact mechanism by which these newborn neurons influence behavior remains unknown. Here, we will examine the contribution of hippocampal neurogenesis to the output of the HPC, and suggest that the role of neurogenesis may vary along the DV axis. Next, we will review literature indicating that anatomical connectivity varies along the DV axis of the HPC, and that this underlies the functional segregation along this axis. This analysis will allow us to synthesize novel hypotheses for the differential contribution of the HPC to cognition and mood.